Pengaruh Konsep Diri dan Regulasi Emosi terhadap Burnout Akademik pada Mahasiswa - M. Luthfi Fauzy; Murtinah Murtinah; Pingkan Sulystiowati; Lucky Purwantini (JURNAL ILMIAH NUSANTARA, 2026)
educational demands that may lead to decreased academic performance and mental health. This study aimed to examine the effects of self-concept and emotion regulation on academic burnout among university students, both partially and simultaneously. The research employed a quantitative correlational method with a sample of 134 students selected using a convenience sampling technique. Data were collected using Likert-scale instruments for all three variables, which demonstrated good content validity (Aiken’s V > 0.80) and high reliability (Cronbach’s Alpha > 0.90). Data analysis was conducted using multiple regression analysis. The results indicated that, simultaneously, self-concept and emotion regulation had a significant effect on academic burnout, with F(2, 131) = 47.98, p < 0.001, and accounted for 42.3% of the variance (R² = 0.423). Partially, self-concept was found to be the strongest predictor in reducing academic burnout (β = 0.50, p < 0.001) compared to emotion regulation (β = 0.16, p = 0.008). These findings highlight the importance of strengthening students’ internal resources, particularly positive perceptions of self-competence, as a primary strategy for minimizing the risk of burnout syndrome in higher education settings.